Design, Manufacturing, and Evaluation a Greenhouse Misting System for Edible Mushroom Production - Mohsen Azadbakht; Reza Naseri; Mohammad Javad Mahmoodi; Mohammad Vahedi Torshizi (Biomechanism and Bioenergy Research)
Rising global food demand necessitates reducing losses through innovative technologies like greenhouse systems. This research compared and examined the performance of mushroom products in moistened and non-moistened treatments. The research was conducted to investigate the effectiveness of environmental control circuits in two main stages of growing button mushroom. In the first stage, the design of the environmental control circuit and moisture of the mushroom growth chamber were addressed. In the second stage, practical use of a moisture control circuit was applied in the mushroom growth chamber and a complete process of growing button mushroom was carried out. The results showed that mushroom in moistened treatment had significant changes in color and weight characteristics of samples, which had a positive impact. Also, using moisture resulted in less browning index and color changes in all samples. Additionally, weight changes in samples were lower when using a moisture control device. Finally, the results obtained showed that the use of 5% moisture treatment reduced weight changes by 4% and also increased the surface area of the mushroom caps by 13%.